Bridging Communication Gaps in Healthcare: An Applied Linguistics Perspective on Patient-Practitioner Interactions - Sari, Nara; Pudyastuti, Zusana E. (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
Effective communication is crucial in healthcare for ensuring patient safety, improving outcomes, and enhancing satisfaction. This study examined healthcare communication through the lens of applied linguistics, focusing on themes outlined by Candlin and Candlin (2003), including interpreters, narratives, risk, patient-practitioner interactions, and critical accounts. Interviews with seven healthcare practitioners in Indonesia and Finland reveal challenges such as language diversity and limited access to interpreter services, leading to reliance on informal strategies like gestures and family involvement. The findings highlight the importance of cultural competence in bridging communication gaps, emphasizing its role in addressing patient needs and fostering trust. Additionally, the study underscores the potential of therapeutic communication training and technology-driven solutions, such as telehealth interpreting services, to enhance healthcare interactions. By integrating linguistic insights, the research advocates for collaborative, multidisciplinary efforts to improve communication practices in diverse healthcare settings. Future studies should explore cultural competence training and innovative technological approaches to address language-related challenges in healthcare.